تحديد مستوى الالتزام التنظيمي للعاملين في القطاع المصرفي دراسة ميدانية على المصارف التجارية بمحافظة اللاذقية - ميا علي; الكنج ربى (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The objective of the research is to determine the level of organizational commitment in its dimensions: emotional, continuous and standard in the commercial banks in Lattakia Governorate, and come out with a set of proposals that can contribute to strengthening the organizational commitment of the employees of the banks under study. The research was based on the descriptive approach and the survey method. The questionnaire was used as the main source of data and information. (150) questionnaires were distributed to the workers, 141 of them were returned to complete questionnaire valid for the statistical analysis, with a response rate of (94%) of the total number of workers in the commercial banks in Lattakia Governorate. ). The results showed that the level of organizational commitment among the employees of the commercial banks under study is high and with relative importance (69.98%). (69.93%) followed by the moral obligation and the relative importance of (67.23%). The most important organizational commitment is the emotional commitment and the relative importance of (72.68%). هدف البحث إلى تحديد مستوى الالتزام التنظيمي بأبعاده: العاطفي والمستمر والمعياري في المصارف التجارية بمحافظة اللاذقية, والخروج بمجموعة من المقترحات التي يمكن أن تسهم في تعزيز الالتزام التنظيمي لدى العاملين في المصارف محل الدراسة.اعتمد البحث على المنهج الوصفي, وأسلوب المسح, حيث اُستخدمت الاستبانة كمصدر رئيس في الحصول على البيانات والمعلومات. وتكون مجتمع البحث من جميع العاملين في المصارف التجارية بمحافظة اللاذقية, ونظراً لصغر حجم مجتمع البحث تمّ اعتماد طريقة الحصر الشامل, حيث تمّ توزيع (150) استبانة على العاملين, وأعيد منها (141) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (94%). أظهرت النتائج أنّ مستوى الالتزام التنظيمي لدى العاملين في المصارف التجارية محل الدراسة هو مستوى مرتفع, وبأهمية نسبية (69.98%). حيث أنّ مستوى الالتزام التنظيمي السائد هو الالتزام الشعوري (العاطفي), وبأهمية نسبية (72.68%), يليه الالتزام المستمر (المتواصل), وبأهمية نسبية (69.93%), يليه الالتزام المعياري (الأخلاقي), وبأهمية نسبية (67.23%).